PERAN KOMITE SEKOLAH DALAM PENGUATAN (SPMI) MELALUI PERENCANAAN DAN EVALUASI (RAKS) - Nur Fadhilah; Khairunnisa Azzahra; Nada Shofa Lubis (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2026)
This study is motivated by the limited involvement of school committees in the implementation of the Internal Quality Assurance System (SPMI), particularly in the planning and evaluation of the School Activity Action Plan (RAKS). The study aims to analyze the role of school committees in strengthening SPMI through the planning and evaluation stages of RAKS at TKIT Khoirul Wildan. A descriptive qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the Miles, Huberman, and Saldana model. The findings reveal that the involvement of the school committee remains at a low level. The committee is not involved in the initial formulation of RAKS and only participates after the document has been finalized. In the evaluation stage, the committee is also not engaged in monitoring or assessing program outcomes, indicating that the advisory and controlling functions have not been optimally implemented within the PPEPP cycle. Although communication between the school and committee is good and the committee has adequate capacity, the absence of formal involvement mechanisms is the main limiting factor. The study concludes that strengthening school–committee partnerships through formal participation mechanisms in SPMI is essential to achieve more participatory, accountable, and sustainable quality management in schools